Local and transboundary transmissions of methicillin-resistant Staphylococcus aureus sequence type 398 through pig trading - Pirolo, M.; Sieber, R.N.; Moodley, Arshnee; Visaggio, D.; Artuso, I.; Gioffrè, A.; Casalinuovo, F.; Spatari, G.; Guardabassi, L.; Stegger, M.; Visca, P. (American Society for Microbiology, 2020)
Livestock-associated methicillin-resistant Staphylococcus aureus sequence type (ST) 398 (LA-MRSA ST398) is a genetic lineage for which pigs are regarded as the main reservoir. An increasing prevalence of LA-MRSA ST398 has been reported in areas with high livestock density throughout Europe. In this study, we investigated the drivers contributing to the introduction and spread of LA-MRSA ST398 through the pig farming system in southern Italy. Whole-genome sequencing (WGS) of LA-MRSA ST398 isolates collected in 2018 from pigs (n = 53) and employees (n = 14) from 10 farms in the Calabria region of Italy were comparatively analyzed with previously published WGS data from Italian ST398 isolates (n = 45), an international ST398 reference collection (n = 89), and isolates from Danish pig farms (n = 283), which are the main suppliers of pigs imported to Italy. Single-nucleotide polymorphisms (SNP) were used to infer isolate relatedness, and these data were used together with data from animal trading to identify factors contributing to LA-MRSA ST398 dissemination. The analyses support the existence of two concurrent pathways for the spread of LA-MRSA ST398 in southern Italy: (i) multiple introductions of LA-MRSA ST398 through the import of colonized pigs from other European countries, including Denmark and France, and (ii) the spread of distinct clones dependent on local trading of pigs between farms. Phylogenetically related Italian and Danish LA-MRSA ST398 isolates shared extensive similarities, including carriage of antimicrobial resistance genes. Our findings highlight the potential risk of transboundary transmission of antimicrobial-resistant bacterial clones with a high zoonotic potential during import of pigs from countries with high LA-MRSA prevalence. IMPORTANCE Over the past decade, livestock-associated methicillin-resistant Staphylococcus aureus sequence type 398 (LA-MRSA ST398) has spread among pig holdings throughout Europe, in parallel with the increased incidence of infections among humans, especially in intensive pig farming regions. Despite the growing prevalence of LA-MRSA ST398 in Italian pig farms, the transmission dynamics of this clone in Italy remains unclear. This work provides genome-based evidence to suggest transboundary LA-MRSA ST398 transmission through trading of colonized pigs between European countries and Italy, as well as between farms in the same Italian region. Our findings show that both international trading and local trading of colonized pigs are important factors contributing to the global spread of LA-MRSA ST398 and underscore the need for control measures on and off the farm to reduce the dissemination of this zoonotic pathogen.